EZH2 Influences mdDA Neuronal Differentiation, Maintenance and Survival - Wever, Iris; von Oerthel, Lars; Wagemans, Cindy M. R. J.; Smidt, Marten P. (Frontiers in Molecular Neuroscience, 2019)
Over the last decade several components have been identified to be differentially expressed in subsets of mesodiencephalic dopaminergic (mdDA) neurons. These differences in molecular profile have been implied to be involved in the selective degeneration of the SNc neurons in Parkinson’s disease. The emergence and maintenance of individual subsets is dependent on different transcriptional programs already present during development. In addition to the influence of transcription factors, recent studies have led to the hypothesis that modifications of histones might also influence the developmental program of neurons. In this study we focus on the histone methyltransferase EZH2 and its role in the development and maintenance of mdDA neurons. We generated two different conditional knock out (cKO) mice; an En1Cre driven cKO, for deletion of Ezh2 in mdDA progenitors and a Pitx3Cre driven cKO, to study the effect of post-mitotic deletion of Ezh2 on mdDA neurons maturation and neuronal survival. During development Ezh2 was found to be important for the generation of the proper amount of TH+ neurons. The loss of neurons primarily affected a rostrolateral population, which is also reflected in the analysis of the subset marks, Ahd2 and Cck. In contrast to early genetic ablation, post-mitotic deletion of Ezh2 did not lead to major developmental defects at E14.5. However, in 6 months old animals Cck was found ectopically in the rostral domain of mdDA neurons and Ahd2 expression was reduced in more mediocaudal positioned cells. In addition, Pitx3Cre driven deletion of Ezh2 led to a progressive loss of TH+ cells in the VTA and these animals display reduced climbing behavior. Together, our data demonstrates that Ezh2 is important for the generation of mdDA neurons during development and that during adult stages Ezh2 is important for the preservation of proper neuronal subset identity and survival.